Long-term Vertigo Control and Vestibular Function After Low-dose On-demand Transtympanic Gentamicin for Refractory Menière's Disease. Issue 2 (February 2019) - Nicolas, Sarah; Kmeid, Michel; Mansour, Charles; Fraysse, Bernard; Deguine, Olivier; Marx, Mathieu; Fraysse, Marie-José Esteve
Abstract : Objective: To describe the long-term clinical vertigo control along with measured lateral canal vestibular function in patients with unilateral refractory Menière's disease (MD) treated with gentamicin transtympanic injections (TTI). Study Design: Retrospective analytic study. Setting: Tertiary referral center. Patients: Thirty-eight patients treated by TTI for medically refractory unilateral MD, defined by the 1995 AAO-HNS criteria, between May 2006 and December 2012. Intervention(s): One-year course of treatment with gentamicin TTI following a low dose on-demand protocol. TTI were repeated in new courses of treatment when MD recurrence occurred. Main Outcome Measure(s): AAO-HNS class of control, caloric tests (CalT), recurrence rate. Results: After an average clinical follow-up of 71 months, all patients entered a class of control A (78%) or B (22%), with an average of 2.3 TTI received. The mean maximal obtained deficit was 88.5%, and the mean long-term deficit was 85.5%. Ten (26%) patients had disease recurrence requiring a new course of treatment. A value of the first CalT in the 3 months following the first TTI strictly higher than 78% was significantly associated with disease control and the absence of symptom recurrence ( p ⩽0.01). In the "recurrence" group, four patients had a significantly lower mean value of all CalT performed after the first TTI when compared with other patients ( p ⩽0.001), indicating gentamicin resistance Conclusion: Achieving a sustainable vestibular deficit on caloric testing is key for MD symptom control after gentamicin TTI. Gentamicin resistance must be diagnosed early to adapt therapeutic strategies.